Beyoğlu, Cezayir Çıkmazı Ve Çevresi Kentsel Yenileme Alanı  Tarihsel Gelişim Ve Koruma Önerileri - Alioğlu, Betül (Fen Bilimleri Enstitüsü, 2015)
Beyoğlu, Vavassore’ye ait 1520 tarihli gravürde “Vigne di Pera” ismiyle ve çitlerle çevrili bahçeli evlerin görüldüğü bir bölge olarak tasvir edilmiştir. Alanın 19. yüzyılda, batılı tarzda inşa edilmiş yüksek katlı, kârgir apartmanların bulunduğu bir bölgeye dönüşmesi süreci 17. yüzyılda elçiliklerin bu alana yerleşmesiyle birlikte başlamıştır. Beyoğlu Kentsel Sit Alanı sınırları içinde bulunan çalışma bölgesinin kentsel yenileme alanı ilan edilmiş olması ile birlikte dönüşüm sürecinde, alanda olabilecek kimlik ve doku kaybından endişe duyulması, alanın tez konusu olarak seçilmesinde başlıca etken olmuştur. Olası kayıplar yaşanmadan bölgenin güncel durumunun belgelenmesi ve tarihsel süreç içindeki değişimin gözlenmesi, elde edilen sonuçlar çerçevesinde bölgenin geleceğine dair koruma önerileri üretilmesi amaçlanmıştır. Çalışmanın merkezini oluşturan “Cezayir Çıkmazı ve Çevresi Kentsel Yenileme Alanı” çevresinden bağımsız değerlendirilemeyeceğinden, çevresindeki komşu yapı adaları ile birlikte ele alınmıştır. 323, 324, 492 ve 493 numaralı yapı adalarından meydana gelen “Cezayir Çıkmazı ve Çevresi Kentsel Yenileme Alanı”nda 52 adet; kentsel yenileme alanının komşu yapı adalarını oluşturan 317, 325, 329, 490 ve 508 numaralı yapı adalarında 138 adet olmak üzere, çalışma alanında toplam 190 adet kültür varlığı bulunmaktadır. %96’sında yapı, kalan bölümünde ise boş arsalar, çeşmeler, hazire, park, trafo ve tuvalet yer alan 287 adet parsel toplam 302 öğeden meydana gelmektedir. Tüm bölgeyi kapsayan güncel analizler ve araştırmalar sonucunda; bölgedeki öğelerin %79’unun tamamen kullanıldığı, %83’ünün şahıslara ait olduğu ve % 65’inin tescilli olduğu tespit edilmiştir. Tescilli 196 adet öğenin %51’inin işlevsel özgünlüğü devam etmektedir. Çalışma alanında bulunan 293 adet yapının %61’inin strüktür sistemi kârgir, %70’inin strüktür durumu iyi durumdadır. Yapıların alt ve üst katlarında yer alan işlevler farklılık göstermektedir. %41’inin zemin katında ticaret işlevi bulunurken üst katların %58’i konut işlevine sahiptir. Kültür varlığı olarak tespit edilmiş yapıların durumunun belgelenmesi amacıyla, yapılara ait envanter fişleri oluşturulmuştur. Kentsel yenileme alanı ilan edilen bölgedeki 52 adet kültür varlığının, Pervititch ve Suat Nirven haritalarındaki durumu ile günümüzdeki durumu karşılaştırılarak, bölge daha detaylı olarak ele alınmıştır. Özgün işlevlerin çoğunlukla devam ettiği gözlenen bölgede; İstiklal Caddesi üzerindeki ve Cezayir Sokağı’nın iki yanında bulunan yapıların çoğunun tamamen ticaret işlevine sahip olduğu; Yeni Çarşı, Boğazkesen, Bostan Başı ve Çukurcuma caddelerinde bulunanların konut + ticaret; Bostaniçi Çeşme, Tercüman ve Selatin Odaları Çıkmazı sokaklarında bulunan yapıların ise genellikle konut işlevine sahip olduğu görülmektedir. Konut ve ticaret işlevinin hakim olduğu bölgede; dini ve kültürel yapılar, konsolosluklar, çeşmeler, oteller ve eğitim yapıları da yer almaktadır. Konsolosluk yapıları işlevsel yoğunluk açısından küçük bir orana sahip olsa da,bölgede bulunan İtalya, Fransa, Hollanda ve Rusya Konsolosluklarına ait parsellerin çalışma alanının yaklaşık üçte birine karşılık geldiği tespit edilmiştir. Bölgede bulunan başlıca dini yapılar; Tomtom Kaptan ve Bostaniçi camileri; Terra Sancta Şapeli, Saint Louis Hollanda Kilisesi ve Maria Draperis Kilisesi; eğitim yapıları; Pierre Loti İlköğretim Okulu ve Beyoğlu Anadolu Lisesi; çeşmeler ise Bostaniçi Camii, Tomtom ve Ömer Ağa çeşmeleridir. 2010 yılında Beyoğlu Belediyesi tarafından onaylanan Beyoğlu Kentsel Sit Alanı Koruma Amaçlı Uygulama İmar Planı, 2013 yılında, İstanbul 10’uncu İdare Mahkemesi tarafından iptal edilmiştir. Beyoğlu Belediyesi Plan Proje Müdürlüğü yetkilileri, tez çalışma alanını kapsayan bölgeye ait alınan kararların yeni hazırlanan projede de benzer şekilde bulunacağını ifade etmişlerdir. Tez kapsamında, Beyoğlu Kentsel Sit Alanı Koruma Amaçlı Uygulama İmar Planı için öneriler bölümünde iptal edilen plan göz önünde bulundurularak değerlendirme yapılmıştır. 2004 yılında “Fransız Sokağı” projesi kapsamında konut bölgesi olan alandaki yapıların neredeyse tüm katları, kafe ve restorana dönüştürülmüş, ancak açılan lüks restoranlar, sanat galerileri ve dükkanlar, beklenen ilgiyi görmemiştir. Çevresinden bağımsız olarak ele alınan projenin, hedefine ulaşmadığı gözlenmektedir. Buna karşılık, Beyoğlu Kentsel Sit Alanı Koruma Amaçlı Uygulama İmar Planı, Cezayir Sokağı’nın yer aldığı iki yapı adasında bulunan tüm yapılar için ticaret + hizmet + turizm işlevlerini önermektedir. Bu tez kapsamında, bölgedeki güncel problemler ve tarihsel süreç göz önünde bulundurularak, alandaki binaların zemin katlarının ticaret , üst katlarının ise konut olarak kullanılması önerilmiştir. Bölge ile ilgili planların yanı sıra, güncel analizler sonucunda; strüktür ve korunmuşluk durumu kötü ya da orta olarak değerlendirilen; ilave katları bulunan; işlevsel özgünlüğü devam etmeyen yapılar bulunduğu tespit edilmiştir. Belirlenen sorunlara yönelik koruma önerileri; basit onarım; kapsamlı onarım; rekonstrüksiyon ve işlev değişikliği olarak geliştirilmiştir. Tez çalışması sonucunda, tespit edilen işlevsel ve yapısal sorunlara bir çözüm bulmak amacıyla geliştirilen koruma önerileri ile birlikte, bölgenin yaşatılarak korunması hedeflenmektedir.

In Vavassore's 1520 dated engraving, “Vigne di Pera”, Beyoğlu is depicted with garden houses enclosed in fences. After the embassies began to settle in this area in the 17th century, it was transformed to an area having Western-style high-rise, masonry buildings built in the 19th century. Pera was shown out of Galata walls in the oldest known engraving about Konstantinopolis, drawn by Christoforo Buondelmonte in 1422 . Although, it was agreed with Genoese to destroy the walls before, the city’s conquest, it existed until 19th century. Italian traders are ingrained in the heart of Galata , the area close to the city walls , the Latin cult members, after the 16th century from the Ottoman embassies began to live . In the mid- 17th century , as well as Turkish Cypriot , the majority of the population of Armenians and Jews reside within the walls of Istanbul , while Europeans were living in Galata and Pera. Thus, foreign embassies such as Dutch, Genoese, French, Venetian, British and christian Ottoman citizens, began to settle in Pera in 1645, that soon turned into an upper class residential area. While Pera was devoloping as a residential area, Galata could keep its trade center character. The population of the region is mainly constituted of Greek, Frankish, Armenian and Turkish residents. Aubry Mortaye a voyager who traveled in 1732 in Galata and Beyoğlu, described the region as a “Frankish district” that consists of embassy buildings. Pera was developing as an European neighborhood in 18th and 19th centuries, but the most intense period began after 1838. Between 1919 and 1922 the life was slow and monotonous in old, İstanbul while in Beyoğlu there was a modern and European social life. After Ankara was named as the capital of the new Turkish Republic and all the embassies moved, Pera gradually began to fade. The study area located in Beyoğlu Urban Site Area boundary has also been declared as an urban renewal area. With the region's declaration as urban renewal area, the loss of identity and of the urban tissue in the transformation process has been the main reason for selecting the area as the subject of this thesis. Documentation of the current status of the region without experiencing such loss, observation of changes in the historical process and in the framework of the results obtained, producing conservation proposals regarding the future of the area is intended. In order to document the condition of the registered buildings, inventory charts of the structures have been created. In addition, the cultural assets, in the area declared as urban renewal area, have been discussed in more detail by comparing the current situation of the area with its situation in Pervititch and Suat Nirven maps. Forming the center of the study, since “Urban Renewal Area of Beyoğlu, Cezayir Cul-De-Sac (section B) and its vicinity” (section of A) cannot be assessed independently, without its surroundings, the area is discussed with its adjacent city blocks. There are 138 listed building in section A, 52 listed building in section of B, 190 listed buildings in total in the working area. As a result of the current analysis and research covering the entire region; more than sixty percent of the structures have been identified as cultural assets that are to be protected. “Urban Renewal Area of Beyoğlu, Cezayir Cul-De-Sac and its vicinity” is consisting of by nine city blocks, that 317, 323, 324, 325 and 329 city blocks in Tomtom neigborhood; 508, 490, 492 and 493 city blocks in Firuzağa neigborhood. The working site, covers an area of approximately 120.460 m2 area, is situated between Nuri Ziya Street in the north, Kumbaracı and Örmealtı Streets in the south, Boğazkesen, Hayriye and Çukurcuma in the east and Istiklal Street in the west. The working area has 287 plots, that %96 of them, including buildings.The remaining part is consisting of vacant lots, fountains, tomb, park and transformer station. The 302 properties in the area are analyzed, determining usage, conservation status, construction materials and stability, ownership, function of ground and upper floors. This analysis revealed, that 79% of the buildings are entirely used, 83% of are owned by private ownership , 65% of them are listed. Of the 293 buildings, 61% are masonary structure, %70 are in good structural stability, 41% have commercial functions on ground floors while and 58% have residential function. 196 building are listed, 51% of them keep their original function. In the region, where the continuation of the original function is observed; most of the buildings on İstiklal Street and each side of the Cezayir Street have commercial functions; the ones in the Yeni Çarşı, Boğazkesen, Bostan Başı and Çukurcuma Streets have residential + trade functions; the ones in Bostaniçi Fountain, Tercüman and Selatin Odaları cul-de-sacs has been observed to have mainly residential functions. The region, where residential and commercial functions dominate also includes religious and cultural buildings, embassies, fountains, hotels and education buildings. Although, the Consulate buildings hold a small proportion in terms of structure and functional density, the parcels of the Consulates of Italy, France, the Netherlands and Russia occupy about one-third of the working area. The main religious buildings in the area are; Tomtom Kaptan and Bostaniçi Mosques; Terra Sancta Chapel, Saint Louis Netherlands Church and Maria Draperis Church. The main educational buildings in the area are Pierre Loti Elementary School and Beyoğlu High School, and the fountains in the area are; Bostaniçi,Tomtom and Ömer Ağa fountains. The Beyoglu Urban Site Area Conservation Implementation Plan approved in 2010 by the Beyoğlu Municipality has been canceled by Istanbul 10th Administrative Court in 2013. The responsables of Beyoğlu Municipality Plan Project Directorate have stated that, no great change is envisaged in the new projects fot the district covering the area of the thesis. In the frame of the thesis, in the section having proposals for Beyoglu Urban Site Area Conservation Implementation Plan, evaluation was made by taking the canceled plan into consideration. Planing of streets and condition of buildings have been evolved by projects and rules which may are the results of natural disasters and special projects for the region. It is known that about 60 fires was occurred between 1615 and 1694 and 27 between 1778- 1795 in Beyoğlu. The biggest and most devastating fire occured in 1870 in Tarlabaşı, Mis, Sakızağacı and Kalyoncukulluğu Streets, Ağa Camii Quarter and in the vicinity of the Italian embassy. Public works and city planning problems have been solved only by orders until 19th century. ‘Ebniye Nizamnamesi’ was the first regulation in 1807, about solving the problems of narrow streets and wooden buildings. Also, regulations of 1826, named “Men-i Harik Nizamnamesi” and “Ebniye Nizamnamesi” in 1848-1849 are known as other main rules that enabled to take some measures against fires. In 2004 under the “French Street” project all floors of the buildings in the housing area have been restored in a way to have cafe and restaurant functions. The newly opened luxury restaurants, art galleries and shops have not had the desired interest. It is observed that the project which has been handled independently without its surrounding has not reached its target. In contrast, Beyoglu Urban Site Area Conservation Implementation Plan proposes a legend that has commerce + service + tourism functions for all the buildings on the two city blocks where Cezayir Street is located. In the context of this thesis, taking current problems of the area and its historic evolution into consideration, it is recommended to use the ground floors of the buildings for commercial functions and the upper floors for residential functions. By comparing the current situation of the area with its situation in the past, some conservation problems are identified: unification and changes in the size of lots changes in the functions of the buildings, lack of communication between the Ist Renewal Area and IInd Cultural and Natural Heritage Preservation Regional Directorate. The result of the current analysis revealed that structures were in majority in bad or moderate structure and preservation status; additional layers; change in original functional specifications. Conservation proposals for identified problems have been developed as; simple maintenance; comprehensive maintenance; reconstruction and proposals of change in function by Cultural and Natural Heritage Preservation Regional Directorate’s rule of 660 numbered decision of principle. In this study, it is proposed to fix architectural components, which are decomposed and ruined, with original ones and recondition the exterior plasters. Reinforcing the structure, removing the additions of poor quality and extra stories, changing proportion of façade, cleaning of façade and adding the original architectural components are determinated by comprehensive maintenance. Nowadays, if there is enough information about old buildings, the reconstruction its made in the pretext of giving back the integrity to the historic sites. French Street, Tomtom Gardens and Beyoglu Urban Site Area Conservation Implementation Plan will certainly result in the gentrification of the area, and changes in the, social, cultural and economic life will accompany this process. In this thesis , Beyoglu Urban Conservation Areas Conservation Master Plan Study layouts were examined and it was found that the studies are insufficient . Many of the interventions formulated by this plan will affect the local residents who are not involved in the decision making process. This thesis along with the developed conservation proposals for the detected functional and structural problems, aims the protection of the area by keeping it authentic and alive.
Urban Renewal Area Of Beyoğlu, Cezayir Cul-de-sac And Its Vicinity Historical Development And Conservation Proposals
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Fransız Sokağı; Kentsel Koruma; Cezayir Sokağı; Tomtom Mahallesi; Knetsel Koruma; French Street; CEZAYİR CUL-DE-SAC; URBAN RENEWAL AREA